Nickel-Catalyzed Ligand-Free Hiyama Coupling of Aryl Bromides and Vinyltrimethoxysilane - Wei, Shichao; Mao, Yongjun; Shi, Shi-Liang (Synlett, 2021)
We herein disclose the first Ni-catalyzed Hiyama coupling of aryl halides with vinylsilanes. This protocol uses cheap, nontoxic, and stable vinyltrimethoxysilane as the vinyl donor, proceeds under mild and ligand-free conditions, furnishing a diverse variety of styrene derivatives in high yields with excellent functional group compatibility.
Keywords: nickel catalysis; vinylation; cross-coupling; Hiyama coupling; ligand-free conditions; vinylsilane; aryl halide